2022
DOI: 10.1186/s12960-022-00735-y
|View full text |Cite
|
Sign up to set email alerts
|

An overview of health workforce education and accreditation in Africa: implications for scaling-up capacity and quality

Abstract: Background For countries to achieve universal health coverage, they need to have well-functioning and resilient health systems. Achieving this requires a sufficient number of qualified health workers and this necessitates the importance of investments in producing and regulating health workers. It is projected that by 2030, Africa would need additional 6.1 million doctors, nurses, and midwives. However, based on the current trajectory, only 3.1 million would be trained and ready for service del… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 23 publications
0
23
0
Order By: Relevance
“…As we were unable to review curricula for both public and private institutions, we cannot say if standards differ between type of institution. A review done in the African region during 2018 revealed that two, nine, 84 and 71 nursing and midwifery institutions exist in Benin, Malawi, Tanzania and Uganda respectively but not sector details are provided for these countries [33]. Assessing curricula is one track followed to measure quality of pre-service education but does not capture key information on the quality of training provided, the educational content delivered in the classroom nor in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As we were unable to review curricula for both public and private institutions, we cannot say if standards differ between type of institution. A review done in the African region during 2018 revealed that two, nine, 84 and 71 nursing and midwifery institutions exist in Benin, Malawi, Tanzania and Uganda respectively but not sector details are provided for these countries [33]. Assessing curricula is one track followed to measure quality of pre-service education but does not capture key information on the quality of training provided, the educational content delivered in the classroom nor in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…As we were unable to review curricula for both public and private institutions, we cannot say if standards differ between type of institution. A review done in the African region during 2018 revealed that two, nine, 84 and 71 nursing and midwifery institutions exist in Benin, Malawi, Tanzania and Uganda respectively but not sector details are provided for these countries [33].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…As we were unable to review curricula for both public and private institutions, we cannot say if standards differ between type of institution. A review done in the African region during 2018 revealed that two, nine, 84 and 71 nursing and midwifery institutions exist in Benin, Malawi, Tanzania and Uganda respectively but no sector details are provided for these countries [33].…”
Section: Discussionmentioning
confidence: 99%
“…There are also other important aspects that this study did not cover such as the regulation of training programmes, the assessment of training institutions and accreditation. However, a recent study highlighted the need for better global, regional and national alignment with professional regulation and practice as the current systems have hindered service delivery and progress towards achieving universal health coverage [33]. Midwife trainees and pre-service training educators perspectives on the curricula content, usefulness and implementation were not assessed in this review, and would be important views to further illuminate, enhance and elaborate on our review findings.…”
Section: Plos Global Public Healthmentioning
confidence: 99%